Consumers' acceptance of locally produced snack-Agromas (chip ubi kayu) / Norfariza Nordin - Nordin, Norfariza (Faculty of Business and Management, 2006)
This research is to study the consumers' awareness of locally produced snack Agromas-Chip Ubi Kayu in Melaka Area. It contains 5 topics. His study completed after a research has taken place in the period of four month.